IMPLEMENTATION OF IT BALANCED SCORECARD AND COBIT 5 FRAMEWORK IN IT GOVERNANCE MANAGEMENT IN THE LIFE INSURANCE INDUSTRY - Riri Fajriah; Ruci Meiyanti (Bakti Nusantara Institute, 2022)
There are several methods that can be used in evaluating the management of IT Governance in a business organization. Some of them are able to use the IT Balanced Scorecard and COBIT 5.0 framework. The Information Technology Balanced Scorecard has four perspectives, including corporate contribution, customer orientation, operational excellence and future orientation. With the implementation of the IT Balance Scorecard, the performance of business organizations such as life insurance companies is not only measured by the financial benefits, as has often been done, but also considers internal processes. In addition, the implementation of the COBIT 5.0 framework provides a comprehensive framework that helps companies achieve their goals for IT Governance. The purpose of the results of this study is a strategic recommendation for companies to be able to provide improvements in the governance and management environment of information technology in the company as one of the enablers in achieving business goals during the Covid-19 pandemic. The results of the IT governance design are in the form of a roadmap for the implementation of IT governance along with recommendations for 25 COBIT 5 processes which are the evaluation points based on the prioritization of the combination of impact and urgency.